A sustainable company in a consumption driven market: How can the choice process of a conscious customer be simplified - Blomén, Joel; Magnusson, Alfrida (My University, 2019)
This bachelor thesis explores the textile industries sustainability efforts, how the leading sustainability brands are working with sustainability and how their work can be evaluated and visualized in an understandable way for the customers. The work was divided into two main research questions; How does design affect clothes sustainability? and how can we simplify the choice-process for the sustainable-conscious customer? Currently there is a trend in the fashion industry called Fast Fashion. It uses people’s consumption behavior to buy more than they need and has great negative effect on our environment. There are other methodologies that companies can follow to produce and design clothes, which prioritizes sustainability, but very few actually measure the impacts. Finding web shops, or any retailer, that guides the customer’s in a better direction is very rare. By studying the current research on designing for sustainability, interviewing professionals and a researcher, a foundation was made. It is common that designers, even at the most sustainable companies, does not have a name on how they design for sustainability, even though they do. Furthermore, it was very rare with tools that measured the sustainable impact, and the once that did were critiqued. Based on this groundwork the result of research question one was built. To find the answers to research question two, benchmarking, workshops and user studies were conducted. The biggest problems were enabling the information for user’s with completely different knowledge and interest, making the evaluation model more intuitive and reliable and establishing Vindpinad’s identity. The result of research question one was a way to divide companies in the different categorization unaware, aware and progressive. An inquiry was developed to guidance the categorization. It was based on design thinking and it analyses a company through its purpose and methodology when developing a product. Research question two resulted in guidance for further development of Vindpinad’s website, identity and their evaluation model. It had a playful expression, fluctuated the website to be more informative and it had a strong idiom towards Vindpinad’s logo. The questionnaire, together with the developed web shop, will have a bigger audience, make a bigger impact and nudge the consumer into having a more sustainable consumption behaviour.